Expatriate adjustment to cross-cultural learning and development among assignees in Nigeria - Mustapha O. Aliyu; Chux G. Iwu (SA Journal of Human Resource Management)
Orientation: One of the reasons for expatriates’ failure is their inability, as well as that of their families, to adapt and adjust to the host country’s cultural and communication patterns.